Kính ngữ trong tiếng Nhật và ảnh hưởng của kính ngữ trong giao tiếp xã hội - Trần, Thị Trang; Nguyễn, Thị Lan Anh (Tạp chí Giáo dục, 2025)
Keigo, or honorific language in Japanese, reflects cultural values such as respect, humility, and social hierarchy, playing a key role in maintaining harmonious relationships. However, under the influence of globalization and cultural shifts - particularly among younger generations - the use of keigo has become increasingly simplified and inaccurate. This study reviews previous research to clarify the function of keigo and examine its ongoing changes. The study reveals that keigo is not only a form of polite expression but also a marker of social position and interpersonal relationships. However, younger speakers tend to use keigo mechanically, often confusing different levels of formality, especially in educational and workplace settings. This situation highlights the need to reform how keigo is taught, moving beyond rote memorization toward developing contextual awareness and social sensitivity. The study also suggests further research on linguistic shifts among younger generations and their impact on modern Japanese communication culture.